1998
DOI: 10.1192/pb.22.9.537
|View full text |Cite
|
Sign up to set email alerts
|

Care programming and service change in a psychiatric sector

Abstract: The effects of service expansion and change (including joint working with social services) following the provision of a community mental health centre and the introduction of care management were examined by auditing service activity. Data were collected on service provision to 20 randomly selected patients who met the local criteria for care management, and also on the general level of service activity as judged by service contacts for all disciplines. Compared to the baseline period, face to face contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…J. K. Wing et al (1998) have suggested that the Health of the Nation Outcome Scales (HoNOS) could be used routinely as part of CPA. Feeney et al (1998) described the practicalities of putting the care programme approach into operation. They found a sixfold increase in patient contacts with a wider range of health professionals involved.…”
Section: Care Programme Approachmentioning
confidence: 99%
“…J. K. Wing et al (1998) have suggested that the Health of the Nation Outcome Scales (HoNOS) could be used routinely as part of CPA. Feeney et al (1998) described the practicalities of putting the care programme approach into operation. They found a sixfold increase in patient contacts with a wider range of health professionals involved.…”
Section: Care Programme Approachmentioning
confidence: 99%